As estratégias de existência camponesa entre os avicultores vinculados à Copagril - Storti, Irma (2010)
This research deals with the strategies of peasant existence in the poultry linked to Copagril (Agro Industrial Cooperative-Copagril). The Copagril operates in several municipalities in western Paraná of which focus Marechal Cândido Rondon and Toledo. On the one hand there is the expansion of capitalist relations with the poultry, on the other; this activity constitutes a peasant reproduction strategy. The research is divided into three chapters. The first chapter, "Aviculture, cooperatives and peasants", addresses the emergence of cooperatives, the contradictions in Brazilian cooperatives, and the relationship between agricultural cooperatives and farmers. This chapter has outlined three proposals are cooperative in Brazil: a proposal Unicafes of cooperative solidarity, the MST, put into practice in land reform settlements and cooperatives linked to Ocepar (Cooperative Organization of Paraná), which act as companies private. In the second chapter was treated on the trajectory of Copagril since its founding in 1970 until the present day. He was treated also the expansion of Copagril with avian activity and its close relationship between the subordination of the peasants. The cooperative was considered an "agent" of capital in the field. The third chapter "The existence and poultry farmer" is about the non-capitalist relations in modern poultry farming, such as labor, family labor, subsistence production, family labor, family relationships, moral debt, customs, among others.